GEOARKEOLOGI KARST SAROLANGUN, JAMBI - Fadhlan Syuaib Intan (WalennaE, 2018)
Sarolangun Karst belongs to the Sarolangun Regency, preserving the cultural remains of the mesolithic period, which has not been too concerned by environmental researchers, especially geoarchaeology. This is the issue that covers general geological conditions. The purpose of this research is to mapping the surface geology in general as an effort to present geological information related to archeological site. The aim is to know the geomorphological, stratigraphic aspects of the archaeological sites. The research method is done through literature review, survey, field data analysis and interpretation. Environmental observations provide information on the landscape of the study area consisting of terrestrial morphology units, weak wavy morphology, strong corrugated morphology units, and karst morphology units. The rivers are dendritic and rectangular, along with the mature-old river, the Old River, Periodic/Permanent River and the Episodic/Intermittent River. The rocks of prehistoric cave compilers are limestones. The geologic structure is a fracture of the shear fault type. Exploration at Sarolangun Karst has listed 6 cave sites. From the classification of petrology, litik tools made of jasper, chert, basalt and andesite rocks. Rock as a raw material litik, found around caves in both the outcrop and boulder. For obsidian sources are located in Bukit Hulu Simpang and Bukit Legal Tinggi.Karst Sarolangun termasuk wilayah Kabupaten Sarolangun, menyimpan tinggalan budaya yang berasal dari masa mesolitik, yang selama ini belum terlalu diperhatikan oleh peneliti lingkungan, khususnya geoarkeologi. Hal inilah yang menjadi pokok permasalahan yang mencakup kondisi geologi secara umum. Adapun maksud penelitian ini adalah melakukan pemetaan geologi permukaan secara umum sebagai salah satu upaya menyajikan informasi geologi terkait dengan situs arkeologi. Tujuannya adalah untuk mengetahui aspek-aspek geomorfologi, stratigrafi di situs-situs arkeologi. Metode penelitian dilakukan melalui kajian pustaka, survei, analisis data lapangan dan interpretasi. Pengamatan lingkungan memberikan informasi tentang bentang alam daerah penelitian yang terdiri dari satuan morfologi dataran, satuan morfologi bergelombang lemah, satuan morfologi bergelombang kuat, dan satuan morfologi karst. Sungainya berpola aliran dendritik dan rektangular, berstadia Sungai Dewasa-Tua, Sungai Tua, Sungai Periodik/Permanen, dan Sungai Episodik/Intermittent. Batuan penyusun gua prasejarah adalah batugamping. Struktur geologi berupa patahan dari jenis patahan geser. Eksplorasi di Karst Sarolangun telah mendata 6 situs gua. Dari klasifikasi petrologi, alat-alat litik terbuat dari batuan jasper, chert, basal dan andesit. Batuan sebagai bahan baku alat litik, banyak ditemukan di sekitar gua-gua baik dalam bentuk singkapan maupun boulder. Untuk sumber obsidian terdapat di Bukit Hulu Simpang dan Bukit Legal Tinggi.